The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1242/jeb.125104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of skeletal muscle energy availability on protein turnover responses to exercise

Abstract: Skeletal muscle adaptation to exercise training is a consequence of repeated contraction-induced increases in gene expression that lead to the accumulation of functional proteins whose role is to blunt the homeostatic perturbations generated by escalations in energetic demand and substrate turnover. The development of a specific 'exercise phenotype' is the result of new, augmented steady-state mRNA and protein levels that stem from the training stimulus (i.e. endurance or resistance based). Maintaining appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 156 publications
1
31
0
Order By: Relevance
“…It has been shown that AICR activates AMPK by acting as an AMP mimetic that binds to AMP binding sites on intracellular proteins, thus leading to metabolic stress 32 . Exercise-induced AMPK activation also causes metabolic stress, but it simultaneously increases mechanical stress 60 . The reasons for the differences in therapeutic effects between AICAR and exercise are that the mechanical stress is only caused by exercise.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that AICR activates AMPK by acting as an AMP mimetic that binds to AMP binding sites on intracellular proteins, thus leading to metabolic stress 32 . Exercise-induced AMPK activation also causes metabolic stress, but it simultaneously increases mechanical stress 60 . The reasons for the differences in therapeutic effects between AICAR and exercise are that the mechanical stress is only caused by exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient and energy availability play an important role in the modulation of acute and chronic adaptations to both endurance and resistance training, 64 suggesting that an adequate nutritional support should be provided to patients in order to preserve the potential benefits of exercise. 62 Vice versa , unloading blunts the amino acid-induced increase in myofibrillar protein synthesis, further supporting the concept that nutrition and exercise may have potential additive effects, 65 although this aspect deserves further investigation in cancer cachexia.…”
Section: Options For Prevention and Treatmentmentioning
confidence: 99%
“…Exercise alters human homeostasis by different means, with energy metabolism particularly affected by heavy and strenuous activities. From a substantial increase in an expenditure of cellular energy to an up-regulation of proteins involved in all aspects of energy turnover (Smiles et al, 2016), exhaustive exercise is consistently accompanied by considerable changes in various indicators of energy metabolism in the circulation and energy-demanding tissues, such as the brain, heart, or skeletal muscle (Kastellorizios and Burgess, 2015). Specifically, a plethora of blood-based biomarkers have emerged in recent years as effective screening tools used to monitor exhaustive exercise-induced changes in bioenergetics (Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%